2001
DOI: 10.1080/13547500110044780
|View full text |Cite
|
Sign up to set email alerts
|

High urine 1-hydroxypyrene glucuronide concentrations in Linxian, China, an area of high risk for squamous oesophageal cancer

Abstract: Most squamous cell carcinomas of the oesophagus in low-risk populations are attributable to alcohol and tobacco consumption, but the aetiologic agents in many high-risk populations have yet to be definitively identified. Linxian, China has some of the highest oesophageal cancer rates in the world. Recent studies suggest that an association exists between high-level exposure to carcinogenic polycyclic aromatic hydrocarbons (PAHs), such as benzo[a]pyrene (B[a]P), and the development of oesophageal cancer. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In general, the levels of 1-OHPG in this population were considerably higher than what is typically observed among non-smokers in the United States, Europe and Korea, where median levels are approximately 0.3-0.4 pmol/mL [22,23]. The median (interquartile range) urinary concentration of 1-OHPG that we observed was 2.01 pmol/mL (0.95-4.09), which is comparable to levels observed in other populations in Linxian, China [24], northeastern Iran [25], and South Brazil [26], all of which are regions with well-characterized high levels of PAH exposure.…”
Section: Discussionsupporting
confidence: 59%
“…In general, the levels of 1-OHPG in this population were considerably higher than what is typically observed among non-smokers in the United States, Europe and Korea, where median levels are approximately 0.3-0.4 pmol/mL [22,23]. The median (interquartile range) urinary concentration of 1-OHPG that we observed was 2.01 pmol/mL (0.95-4.09), which is comparable to levels observed in other populations in Linxian, China [24], northeastern Iran [25], and South Brazil [26], all of which are regions with well-characterized high levels of PAH exposure.…”
Section: Discussionsupporting
confidence: 59%
“…There is a striking dose-response relationship between the PAH content of non-tumoral esophageal biopsies, and ESCC (37). Previous studies have shown very high levels of urinary 1-hydroxypyrene glucuronide (1-OHPG), a stable short-term PAH metabolite in high-risk areas of Iran and China (38, 39). The level of PAH-related DNA adducts is also very high in Golestan, even among female non-smokers (36).…”
Section: Discussionmentioning
confidence: 99%
“…1-Hydroxypyrene-glucuronide (1-OHPG) is a stable PAH metabolite that is excreted in the urine and is an index biomarker that reflects recent exposure to mixed PAHs 27 . In the present study, we first analysed the association between maternal exposure to PAHs by measuring urine 1-OHPG concentration during pregnancy and the risk of foetal CHDs.…”
Section: Introductionmentioning
confidence: 99%